Yurisdiksi ICC terhadap Negara non Anggota Statuta Roma 1998 - Sefriani Sefriani (Jurnal Hukum IUS QUIA IUSTUM, 2007)
State Parties of Rome Satute 1998 have a territorial  jurisdiction  over the crimes which occured on  their territorial. This is applied for all authors which come from the state parties and non state parties.